Methylenetetrahydrofolate Reductase C677T and A1298C Mutations in Women with Recurrent Spontaneous Abortions in the Northwest of Iran. (14th November 2012) - Poursadegh Zonouzi, Ahmad; Chaparzadeh, Nader; Asghari Estiar, Mehrdad; Mehrzad Sadaghiani, Mahzad; Farzadi, Laya; Ghasemzadeh, Alieh; Sakhinia, Masoud; Sakhinia, Ebrahim
Abstract : Introduction . Recurrent spontaneous abortion (RSA) is a significant obstetrical complication that may occur during pregnancy. Various studies in recent years have indicated that two common mutations (C677T and A1298C) of the methylenetetrahydrofolate reductase (MTHFR) gene are risk factor for RSA. This study was carried out to determine the influence of (C677T and A1298C) of the methylenetetrahydrofolate reductase (MTHFR) gene mutations with RSA. Materials and Methods . A total of 139 women were included in this study: 89 women with two or more consecutive miscarriages and 50 healthy controls. Total genomic DNA was isolated from blood leukocytes. To determine the frequency of the two common C677T and A1298C MTHFR gene mutations in the patients and controls, we used two methods, amplification refractory mutation system-PCR and PCR-restriction fragment length polymorphism. Results . There is no significant difference in the prevalence of 677T/T genotype among women with RSA and healthy controls (P = 0.285 ). Also no statistically significant difference in the frequency of A1298C MTHFR gene mutation was detected between the two groups (P = 0.175 ). Conclusion . In conclusion, the results indicate that the Amplification Refractory Mutation System-PCR method was in complete concordance with the results obtained by standard PCR-restriction fragment length polymorphism method. The results also show no significant difference in MTHFR C677T/A1298C genotype distribution among the two groups; therefore, further studies on larger population and other genetic variants to better understand the pathobiology of RSA are needed.